Buka Tutup Tirai Garasi Otomatis Dengan Sensor Hujan Serta Sensor LDR (Light Dependent Resistor) Berbasis Arduino Uno - Putro, Ivan Fajarianto, Agus Ulinuha, ST., MT., Ph.D (2017)
Garage is a need for the community especially due to the lifestyle of urban communities where the car is already a primary need, considering the limited land,a semi-permanent garage with open-close capability will be good option. Making Open and close the curtains automatically feels is in need because it can petrify human occupation in the car cover rain or at night. Making tools unscrew automatic curtains using a rain sensor and sensor LDR (Light Dependent Resistor) as a basis for machine control Open and close the blinds automatically, as a rain sensor and sensor LDR is used to detect the rainwater and also to detect light at day and night, To drive the appliance automatically open the closed curtain, universal single phase motors are used to open and close the curtains. In automatic dick using Arduino with OR logic so that it will shut down when it rains, night, or both, and open when the day and no rain. Tests were carried out to know the ability of the tool automatically close the curtains open and its reliability as well as testing the combination of the two sensors as the basis for the beginning of the movement of the tool unscrew this automatic curtains.